Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/cells12091307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rho-Associated Kinase (Rock) Inhibitors (Alternative to Y-27632) on Primary Human Corneal Endothelial Cells

Abstract: (1) Rho-associated coiled-coil protein kinase (ROCK) signaling cascade impacts a wide array of cellular events. For cellular therapeutics, scalable expansion of primary human corneal endothelial cells (CECs) is crucial, and the inhibition of ROCK signaling using a well characterized ROCK inhibitor (ROCKi) Y-27632 had been shown to enhance overall endothelial cell yield. (2) In this study, we compared several classes of ROCK inhibitors to both ROCK-I and ROCK-II, using in silico binding simulation. We then eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In addition to opening new therapeutic options in glaucoma, ROCK inhibitors have shown promise in the treatment of corneal endothelial diseases by promoting corneal endothelial cell regeneration and both functional and morphological recovery [4]. Laboratory studies have suggested that ROCK inhibitors improve cellular attachment and proliferation of cultured endothelial cells in vitro and improve wound healing on ex vivo corneas [5]. They facilitate cell cycle progression from the G1 to S phase and prevent actinomyosin contraction by inhibiting the Rho kinase signaling cascade [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to opening new therapeutic options in glaucoma, ROCK inhibitors have shown promise in the treatment of corneal endothelial diseases by promoting corneal endothelial cell regeneration and both functional and morphological recovery [4]. Laboratory studies have suggested that ROCK inhibitors improve cellular attachment and proliferation of cultured endothelial cells in vitro and improve wound healing on ex vivo corneas [5]. They facilitate cell cycle progression from the G1 to S phase and prevent actinomyosin contraction by inhibiting the Rho kinase signaling cascade [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fasudil was originally approved in Japan in 1995 for the treatment of cerebral vasospasms caused by subarachnoid hemorrhage [8], and it is used in ophthalmology for the treatment of diabetic macular edema (DME) [9]. Finally, two ROCK inhibitors have not been approved yet: SNJ-1656, currently in phase II trial for controlling intraocular pressure (IOP) [10], and Y-27632, still in a pre-clinical phase for use in corneal endothelial diseases [5].…”
Section: Introductionmentioning
confidence: 99%